Katarakta pri steklopihalcih - Prelesnik, Uroš (Zdravstveno varstvo, 2004)
Background. High rates of cataract have been recorded among glass workers exposed to high temperatures of glass furnaces, and among glassblowers. Views on exposure risks vary widely. The study included 47 glass workers employed in the Hrastnik Glass Factory as glassblowers for at least 20 years. The analysis was supported by the factory management who wanted to know whether glassblowers were at increased risk for ocular diseases. Methods. From January to July 2002, 47 glassblowers were examined. The results were comparedwith observations for the control group, i.e. 150 age-matched patientswho attended the outpatient clinic at the same time. The subjects were evaluated by a slit lamp examination, examination of visual acuity, with and without correction, by intraocular pressure measurement, eye fundus examination and determination of the visual field. In addition, the subjects' handedness was assessed. Results. The results showed that cataract and deficits of the visual field occurred more frequently in glassblowers than in the control group. There were no differences between the groups concerning themeasured intraocular pressure. Conclusion. The results confirmed our assumption that glassblowers are at a higher risk of developing cataract than the general population. Individuals exposed to IR-irradiation were found to develop cataractous changes earlier and at a higher rate. Hypothetically, visual field deficits can also be induced by IR-irradiation.
Keywords: oftalmologija; poklicne bolezni; siva mrena; steklopihalci